Descripción del sentido de la vida en adolescentes infractores de la ciudad de Medellín (2011)
ABSTRACT: The aim of this research was to compare the meaning of life’s intensity in offender teenagers in Medellin city, Colombia. The methodology had a mixed descriptive design. The sample consisted of 44 young offenders who answered the Purpose In Life test (PIL), developed by Crumbaugh and Maholick, consisting of one party to collect quantitative and two other parties to collect qualitative information. The Results show a low rate of existential vacuum in the teens surveyed. The more time spent in a social rehabilitation institution, the greater the intensity of the meaning of life. The family (real and ideal) is important as a core value around which to build their sense of life. This suggests some grounds for thinking a model to explain the conclusions reached. It argues that the construct “meaning of life” has different levels of complexity that reflect various aspects mentioned below: the desire to live, aim or purpose of life that gives the proper orientation of each existence, the meaning that each one attributes to his life and his different values that govern it, and finally, the analysis of meaning in general.